The 6‐minute walk test and other clinical endpoints in duchenne muscular dystrophy: Reliability, concurrent validity, and minimal clinically important differences from a multicenter study. Issue 3 (17th July 2013) - McDonald, Craig M.; Henricson, Erik K.; Abresch, R. Ted; Florence, Julaine; Eagle, Michelle; Gappmaier, Eduard; Glanzman, Allan M.; ,; Spiegel, Robert; Barth, Jay; Elfring, Gary; Reha, Allen; et al.
ABSTRACT Introduction: An international clinical trial enrolled 174 ambulatory males ≥5 years old with nonsense mutation Duchenne muscular dystrophy (nmDMD). Pretreatment data provide insight into reliability, concurrent validity, and minimal clinically important differences (MCIDs) of the 6‐minute walk test (6MWT) and other endpoints. Methods: Screening and baseline evaluations included the 6‐minute walk distance (6MWD), timed function tests (TFTs), quantitative strength by myometry, the PedsQL, heart rate–determined energy expenditure index, and other exploratory endpoints. Results: The 6MWT proved feasible and reliable in a multicenter context. Concurrent validity with other endpoints was excellent. The MCID for 6MWD was 28.5 and 31.7 meters based on 2 statistical distribution methods. Conclusions: The ratio of MCID to baseline mean is lower for 6MWD than for other endpoints. The 6MWD is an optimal primary endpoint for Duchenne muscular dystrophy (DMD) clinical trials that are focused therapeutically on preservation of ambulation and slowing of disease progression. Muscle Nerve48: 357–368, 2013